The Debt Crisis, the Euro and European Political Integration: Reflections from the Economy (Res Publica. Revista de Historia de las Ideas Políticas, 2015)
This paper examines which direction the sovereign debt crisis will take, considering whether or not there are circumstances that will lead to the integration of the European Union. Germany, as a consolidated economy, although with a misguided vision of the crisis, can choose to act as a cooperative leader or a hegemonic leader, in order to go beyond the current logic of the euro and design a scheme where the ECB has greater weight in the creation of common objectives, which will give new impetus to the project of political union. On the other hand, the paper will also compare the experience of the United States in the area of fiscal union, to conclude that it is necessary to strengthen the idea of political unity in Europe. However, this will be a long journey with an unforeseeable ending.